Politik Hukum Undang-Undang Cipta Kerja Pada Aspek Hubungan Industrial - Ahmad Fadli Fauzi (Lex Renaissance, 2023)
produced only satisfy the political principles and hence are problematic. The issues with the Job Creation Law are not only at the legislative stage; but at the level of normative substance whereby there are several problematic articles. For instance, in terms of wages, the phrase "necessities for a decent living" as regulated in Article 88 has been removed, alterations to Article 151 which have the potential for unilateral layoffs, and the repeal of Article 59 regarding PKWT which was previously regulated in the Employment Law. The formulation of the problem in this article is what are the legal politics in the Job Creation Law, especially in the industrial relations aspect and the implications of the norms of the Law? The research method used is juridical-normative research using a conceptual approach and a statutory approach. Meanwhile, the data used is secondary data which includes primary, secondary and tertiary legal materials. The findings in this article show that the legal politics of the Job Creation Law in the industrial relations aspect only fulfill political rules, but fail to fulfill the rights and interests of workers. Apart from that, several problematic articles were found in the Employment Chapter of the Job Creation Law, for example regarding wages, layoffs, PKWT, and so on. In this regards, the Job Creation Law is unable to address problems in the industrial relations aspect, because at the substantive level, problematic norms have the potential to injure the workers/employees who are in a weaker position.Keywords: Legal Politics, Job Creation Law, Industrial Relations. AbstrakArah kebijakan dalam UU Cipta Kerja tampak bernuansa politis dan tidak terlepas dari negosiasi kepentingan antara penguasa dan pengusaha. Akibatnya, produk hukum yang dihasilkan hanya memenuhi kaidah politis dan problematis. Permasalahan dalam UU Cipta Kerja tidak hanya pada tahap legislasi, namun dalam tataran substansi norma pun terdapat beberapa pasal bermasalah. Misalnya, dalam hal pengupahan dihapusnya frasa “kebutuhan hidup layak” yang diatur dalam Pasal 88, berubahnya Pasal 151 yang berpotensi pada PHK sepihak, dan dicabutnya Pasal 59 terkait PKWT yang sebelumnya diatur dalam UU Ketenagakerjaan. Rumusan masalah dalam artikel ini ialah apa politik hukum dalam UU Cipta Kerja khususnya pada aspek hubungan industrial dan implikasi dari norma-norma UU tersebut? Metode penelitian yang digunakan ialah penelitian yuridis-normatif dengan menggunakan pendekatan konseptual dan pendekatan undang-undang. Sedangkan data yang digunakan ialah data sekunder yang meliputi bahan hukum primer, skunder, dan tersier. Temuan dalam artikel ini menunjukkan bahwa politik hukum UU Cipta Kerja pada aspek hubungan indsutrial hanya memenuhi kaidah politik semata, namun gagal memenuhi hak dan kepentingan buruh. Selain itu, ditemukan beberapa pasal bermasalah dalam UU Cipta Kerja Bab Ketenagakerjaan, misalnya terkait pengupahan, PHK, PKWT, dan sebagainya. Dengan demikian, UU Cipta Kerja tidak dapat menjawab permasalahan dalam aspek hubungan industrial, karena dalam tataran substansi norma yang bermasalah berpotensi merugikan buruh/pekerja yang berada pada posisi lemah.Kata kunci: Politik Hukum, UU Cipta Kerja, Hubungan Industrial.